SISTEM PAKAR UJI KOMPETENSI BAGI SISWA BERKEBUTUHAN KHUSUS AUTIS DENGAN MENGGUNAKAN METODE SINGLE LINKAGE - Suryanto, Baginda; Honggowibowo, Anton Setiawan; Indrianingsih, Yuliani (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2014)
Conventional knowledge test on the learning outcomes that have been given by previous teachers, often making bored students with autism. The results obtained are less accurate and require teachers to perform even the repetition of material grading explanations often not objective. Provision of additional material not often right on target, and even students who need to get a repetition of material often do not get the repetition of material. Expert Systems Competency Test Program for Students with Special Needs Autism is designed with the needs of the school that is the subject of research and data collection. Cluster analysis works by grouping students by similarity score minimum euclidian distance of each data. This program tests every student and provide an explanation for the repetition of questions whose answers are not in accordance with the specified result.Program based on the use of Expert Systems Competency Test for Students with Special Needs Autism, the results obtained grouping students based on their level of intelligence that has been stored in the process of testing the competency test conducted by the students with autism. So that teachers can provide in the future teaching methods to suit the needs of students in order to enhance the level of intelligence of autistic students.